Do LTE service customers have different customer loyalty determinants? - Wonsuk Jung; Youngsun Kwon (International Telecommunications Society (ITS), 2014)
This study explores the determinants of customer loyalty in the Korean mobile telecommunications market with the emphasis on customer satisfaction and switching costs as major predictors of customer loyalty. South Korea has now become one of the world's most leading mobile service markets with the launch of its advanced LTE services; the LTE service subscription rate in Korea has exceeded 50% as of November 2013. This raises a question as to whether LTE service subscribers are different from 3G service subscribers. In this rapidly changing environment of mobile service markets, this study examines the validity of the traditional determinants of customer satisfaction in data-service oriented mobile markets, analyzes the effect of customer satisfaction and switching costs on customer loyalty, and assesses the difference between 3G and LTE subscribers with respect to their determinants of customer loyalty. The results showed that there are significant differences between 3G and LTE subscribers while traditional factors such as call quality, data quality, customer support, and price perception are still significant determinants of customer satisfaction.
Keywords: 330; LTE; 3G; Customer Satisfaction; Switching Cost; Loyalty; Smartphone